Performance of male crossbred (Saanen x Local) goats fed concentrate diet - Rahman, Mohammad Mijanur; Syahmi, M.A.G.; Airina, R.I.R.K.; Abdullah, Ramli (Universiti Putra Malaysia, 2018)
The aim of this study was to assess the performance of concentrate feeding on intake and growth rate in goats. A total of 14 non-castrated male crossbred (Saanen x Local) goats of approximate age of 6 months and average initial live weight of 23.5±3.8 kg were used in a completely randomised design. The animals were divided into two treatment groups: control group and concentrate group. Both groups were fed their respective diets ad libitum throughout the experiment. The goats on the concentrate diet were also supplemented daily with 400 g fresh Napier grass variety for each animal. Chemical composition of the diets, intake and growth rate of the goats were evaluated. No differences (p>0.05) were observed in dry matter and organic matter intakes except for crude protein (CP) and neutral detergent fibre (NDF) (p<0.05). The control group showed higher intakes of CP and NDF compared to the goats in the concentrate group. However, no differences were observed (p>0.05) in the growth performance and feed conversion ratio between the control and concentrate groups. There was no significant effect on daily weight gain of the goats fed the concentrate diets, suggesting that corn and soya waste with 400 g fresh Napier grass can support moderate weight gain in Saanen crossbred goats.